Spirituality and Social Work - Sheridan, Michael (A journal of church and state, 2011)
Following a long period of distancing itself from its sectarian roots, social work began a re-examination of its relationship with religion and spirituality in the 1980s, spurring an explosive number of writings on the subject. These publications generally have highlighted the potential benefits of incorporating attention to the spiritual dimension while highlighting areas of caution and developing ethical guidelines for practice. Two of the most touted rationales for this renewed attention are the profession's holistic framework for understanding the human condition (bio-psycho-social-spiritual) and its commitment to human diversity, including religious and spiritual diversity.